Toxin Production in Clostridium botulinum as Demonstrated by Electron Microscopy - Duda, John J. (1969)
Spheroplasts of Clostridium botulinum 62A were prepared with the use of lysozyme. These spheroplasts were then exposed to ferritin-labeled type A antitoxin. Ultrathin sections of these specimens revealed the ferritin-labeled antibody symmetrically arranged around the outer spore coats but not within the spore cortex. The ferritin-labeled antibody was also observed in the bacterial cytoplasm. Here it was arranged in aggregates and strands, although it was not associated with any identifiable cell structure. Controls included sections of C. botulinum spheroplasts treated with a 1.5% solution of ferritin as well as spheroplasts of C. roseum and Bacillus subtilis treated with conjugated type A antitoxin or a 1.5% solution of ferritin. No intracellular or extracellular ferritin was demonstrable in these specimens.